Formulation Development, In Vitro and In Vivo Evaluation of Topical Hydrogel Formulation of Econazole Nitrate-Loaded β-Cyclodextrin Nanosponges - Srivastava S.; Mahor A.; Singh G.; Bansal K.; Singh P.P.; Gupta R.; Dutt R.; Alanazi A.M.; Khan A.A.; Kesharwani P. (My University, 2025)
Econazole nitrate, an antifungal drug used in the handling of skin ailments, is commercially not efficient as these ailments typically require a more elevated concentration of the drug to offer an effective pharmacological retort. Like so, it is proposed to assess the effectiveness of the topical hydrogel of econazole-loaded nanosponge in the management of skin ailment(s). Econazole nitrate-laden β-cyclodextrin nanosponges were developed by employing the melt method using β-cyclodextrin as the organic polymer and N,N-carbonyldiimidazole as the crosslinker. The critical factors disturbing the quality of the formulation were uniquely identified by the Ishikawa diagram, and they were optimized by the statistical experiment design concept. β-cyclodextrin loaded nanosponges were uniquely designed using the Placket-Burman approach and optimized utilizing the Box-Behnken method. The optimized nanosponges (EN-CDN) were 421.37 ± 6.19 nm in size with an entrapment efficiency of 70.13% ± 5.73%. The topical hydrogel of nanosponges (EN-TG) was prepared using carbopol 934 and pyrrolidone as permeation enhancers. In vitro skin permeation studies affirmed the improved transport crosswise the goatskin for topical hydrogel in comparison to the marketed product. EN-TG was able to control the fungal infection in the selected animal model in comparison to the marketed preparation. Stability studies reported favorably that nanogel remained stable under normal and accelerated settings. © 2021 American Pharmacists Association